ANALYSIS OF MARKETING STRATEGY IMPLEMENTATION IN GYM SPORTS ESPECIALLY FOR MUSLIMS - Lalitta Angelina Bauty (TSARWATICA (Islamic Economic, Accounting, and Management Journal), 2020)
Gym Sport room for women in today is very well-developed as the era and development of life that specializes in women also want to exercise especially Fitness to be able to exercise freely without any need Mixing with the opposite gender in the scope of the sport, because the gym room of women in specialize and removing the staff is not women. This modern era of fitness is known only as sports to form muscles. In fact there are many other benefits besides muscle formation. But in reality the gym room is a sports facility that there are various sports that are very easy to do as for example, gymnastics, aerobics, Zumba and so forth that can make our body to be healthier.